Low toxicity and favorable clinical and quality of life impact after non-myeloablative autologous hematopoietic stem cell transplant in Crohn's disease NCT 03000296 Date 9 December 2016 - Ruiz, Milton Artur [UNESP]; Kaiser, Roberto Luiz; De Quadros, Luiz Gustavo; Piron-Ruiz, Lilian; Peña-Arciniegas, Tatiana; Faria, Mikaell Alexandre Gouvea; Siqueira, Rubens Camargo; Pirozzi, Flavio Fontes; Kaiser, Fernanda Soubhia Liedtke; Burt, Richard K. (Springer Nature, 2017)
Objective: The incidence of adverse events in myeloablative transplant protocols is high in refractory Crohn's disease; this study used low doses of cyclophosphamide. Fourteen patients were submitted to non-myeloablative autologous hematopoietic stem cell transplantation. Results: The average number of days of anemia (hemoglobin < 10 g/dL) was 5.4 ± 4.2 and 14 ± 2.4 in the mobilization and conditioning phases, respectively. The mean number of days of neutropenia (neutrophils < 0.5 × 109/L) in the mobilization phase was 1.7 ± 1.5 while it was 7.6 ± 1.4 in the conditioning phase. When comparing the conditioning and mobilization phases, there was an increased number days of leukopenia (white blood cells < 1.0 × 109/L), lymphocytopenia (lymphocytes < 0.5 × 109/L) and thrombocytopenia (platelets < 25 × 109/L). Crohn's Disease Activity Index values before the transplant ranged from 155 to 450.5 (mean 281.2 ± 79.0) and at 30 days after the procedures they ranged from 45.4 to 177 (mean 95.8 ± 35.4). Moreover, the procedure improved in overall quality of life of patients. Non-myeloablative autologous hematopoietic stem cell transplantation with lower doses of cyclophosphamide leads to lower rates of hematological toxicity and adverse events compared to protocols described in the literature. Trial registration NCT 03000296: Date 9 December 2016